Scholarly use of information for research by postgraduate students: the role of Kenneth Dike Library (KDL) (2013)
Research process is being focused upon by universities and colleges. An important element in the research process is the accessibility of information resources and services provided by libraries. Postgraduate students are one group of stakeholders in the universities. It is thus appropriate for academic libraries to re-examine how they can play a more relevant role in facilitating research. This study examines the views of postgraduate students on the role of the university library in helping them with their research and their satisfaction with the sources and services currently provided. The study adopted descriptive design and questionnaire was used to gather information from postgraduate students. Data were collected from 300 randomly selected postgraduate students from the university. They were analyzed with simple descriptive statistics. The findings show that the majority (55%) of respondents acknowledged the important role of library in facilitating research, while (48.2%) of the respondents were satisfied with the current role being played by the libraries. It is recommended that libraries need to create awareness among postgraduate students about the services and resources that are available and how to use them and academic libraries should be stocked with up-to-date materials in order to encourage researchers to use their facilities.